Bi-metallic Pd/Au nanoparticles prepared by UV-excimer laser exposure. (December 2020) - Schmidl, G.; Raugust, M.; Dellith, J.; Dellith, A.; Schmidl, F.; Bochmann, A.; Plentz, J.
Graphical abstract: Highlights: Particle formation is controlled by laser energy, pulse number, total and individual layer thickness. 2θ-reflex positions of element compositions change according to the percentage ratio of the individual layers. The (111) reflex of the Pd-Au mixed phase becomes larger as the pulse energy increases. A homogeneous distribution of Pd and Au in the particles is shown by EDX. LSPR peaks change with the particle composition. Abstract: Multi-metallic nanoparticles are useful for applications in biophotonics or catalysis. Metal compounds alter the properties of pure metallic nanoparticles and thus expand the particle performance compared to particles consisting of the pure phase of metals. We investigated the formation of bi-metallic Pd/Au nanoparticle systems fabricated by UV excimer laser exposure at 248 nm in the ns range and the structural, the morphological as well as the optical properties of these alloy nanoparticles. Laser parameters like energy and pulse number or the thickness proportions of the individual layers to the total layer thickness were varied. Due to the volume percentage of the metals, the total layer thickness and the used laser parameters, the particle size and size distribution could be tuned. The corresponding nanoparticle formation is able to influence the plasmon resonance in position and in shape. Based on x-ray diffraction measurements and energy dispersive x-ray analysis an alloy formation was observed. Using x-ray diffraction, the formation of additional reflexes of palladium-gold alloys between the reflexes of the pure metals could be detected. Furthermore, the position and intensity was adjustable by the percentage composition of metals. The energy dispersive x-ray analysis showed the spatial presence of both elements in each particle.